(untitled) (Damascus University Journal of agriculture sciences, 2025)
We applied in our study, Recombinant Harpin protein ,which produced locally in Syria,on 10-day wheat seedlings by spraying, to study its effect in increasing wheat resistance by measuring the activity of superoxide dismutase (SOD) enzyme, sterilized distilled water was used as a control, samples collected from plants at (0, 1, 2, 4, 18, 24, 48, 72, 96) hour post-treatment and stored at -70°C, total protein was extracted from frozen samples ,their concentrations were derermined by Bradford assay.